207 CLINICAL FRAILTY SCORE (CFS) IN THE ORTHOGERIATRIC POPULATION: DESCRIPTIVE ANALYSIS AND CHARACTERISTICS. (25th October 2022) - Cloney, T; Crowley, P; Rafferty, M; Gannon, E; Ahern, E
Abstract: Background: In a hospital in the South of Ireland, all older adults admitted with hip and other fragility fractures are co-managed by the Orthopaedic & Orthogeriatric services. Identifying a patient's Clinical Frailty Scale (CFS) has become a standard part of our comprehensive geriatric assessment for this cohort. We reviewed characteristics of those with documented CFS. Methods: We retrospectively reviewed 5 years of the hospital's hip fracture database. The data was downloaded into an Excel spreadsheet where it was formatted and cleaned to binary data to enable accurate assessment. We sub-grouped the cohort based on admission, dating from July 2019 - the onset of co-management care and routine identification and documentation of CFS - to date (September 2021). Results: 1132 adults were admitted with hip fractures between July 1st 2019 and September 30th 2021. 65.8% of admissions were female. 944 (83.4%) had documented CFS. The median CFS is 5. 515 (54.5%) had a score 5 or greater. Of the 944 patients, 83.9% of were admitted from home, 13.7% from nursing home (NH) and 2.4% from an alternative healthcare facility. Frailer patients are more likely to be admitted from NH. 92.3% of patients with documented CFS had a 4-AT administered. 99.7% of patients with documented CFS had a New Mobility Score (NMS) documented. The median NMS was 5. Patients with lower NMS had a higher CFS. 83.4% of people were mobilised day 1 post-operatively, with rates decreasing in frailer patients. The majority of people admitted from home were discharged to rehab (64.5%) and home (22.2%). 2.4% of those admitted from home were discharged to NH, with 95% (18/19) having a CFS 5 of greater. 5.3% of patients died (50/944), with 92% of deaths having a CFS 5 or greater. Conclusion: CFS may offer us information into care planning for the orthogeriatric population. More work needs to be done evaluate its usefulness.